COGNITIVE SCHEMAS AND FRAMES: THE ROLE OF PERSONAL EXPERIENCE IN ACADEMIC TEXT CREATION (Scientific journal of the Fergana State University, 2026)
The article analyzes the role of the author’s cognitive schemas and frames in the process of academic text creation. The theoretical and methodological foundations of cognitive mediation between personal experience and scientific discourse are examined.